Divergence in Cytogenetic and Molecular Genetic Analysis Results: A Case Report of Fragile X Syndrome among Siblings - Elias Marjanu Hikmah; Mamat Norhashimah; Ismail Siti Mariam; Salmi Razak; Pornprot Limprasert; Wanna Sudhikaran; Ravindran Ankathil; Alwi Zilfalil (Japan International Cultural Exchange Foundation, 2024)
Non-Indexed Publication